Analisis Perlokusi Dalam Percakapan Guru Dan Siswa Kelas XI Madrasah Aliyah Nahdlatul Ulama 03 Brebes - Kurniasih Kurniasih; Nurchalistiani Budiana; Robert Rizki Yono (Departement of Mathematics Education, 2024)
The act of speaking involves the production of sounds in words which are very good for expresing thoughts, ideas and emotions. As a communication tool, it not only conveys the speaker’s ideas to the listener, but serves various purposes based on the speaker’s intentions to the listener, but serves various purposes based on the speaker’s intentions. In the realm of communication acts there are 3 different types, namely Locution, Illocution, Perlocution. For research using qualitative methods, this research investigates the occurrence of perlocutionary speech acts in conversations between students and teachers, as well as between students themselves, preferably during learning or when break time arrives. This research serves to highlight the significant impact of context and speech influence, and emphasizes the importance of further studies in this area